Caracterização do conteúdo harmônico em ambientes residenciais: estudo de caso - Carvalho, Flavio Gomes de (2015)
In this work a characterization of harmonic content in residential electrical systems through a set of measurements over various periods of time is performed. For each reported case it was a statement of charges that make up the installation and an individual analysis of each of them as a way to assess their influence on the harmonic behavior of the installation as a whole.